Is Acupuncture Effective on Post-Lumbar Puncture Headache? - Moshtagh, Mozhgan; Soleimanian Asl, Mobin; Esmailzadeh, Mohammad; Momeni, Amirmohammad; Boostani, Amirhossein; Amiri, Rana; Sharafi, Simin (Health Nexus, 2023)
According to the findings of the articles that were picked up until December 27, 2022, using our search strategy in the mentioned databases (1-9), the effectiveness of acupuncture on reducing headache post-dural puncture headaches after lumbar puncture is very ambiguous because these articles do not have the necessary quality to achieve this purpose.  According to the explanations provided, we point out some of the limitations we encountered in the current research:1) Most of the articles in this field were case reports.2) The quality of the articles based on the existing checklists is not optimal.3) The results of the limited studies available were also inconsistent.4) The number of English-language articles in this field was limited.5) The duration of intervention and points used for acupuncture had not been explained in some studies.